Influence of the adoption of technology and labor in productive efficiency in the agricultural sector of Mexico, 1979-2014 - Pérez Fernández, Alberto; Caamal Cauich, Ignacio; Pat Fernández, Verna Gricel; Martínez Luis, David; Reza Salgado, Juventino (Acta Universitaria, 2019)
Economic growth implies the study of productive factors: land, labor, capital, educational level of the population and technology adoption. This research quantifies the effect of production factors on agricultural production in Mexico from 1979 to 2014, by estimating a Cobb-Douglas production function and the Malmquist Index. The results indicate that the use of the surface in irrigation and labor in Mexico are the most important variables for the growth of the agricultural sector, but its use is inefficient; the application of fertilizers, diminishing returns and technical efficiency decreased after the entry into force of the North American Free Trade Agreement (NAFTA). The application of policies for the provision of technology must be accompanied by extension programs and technical advice to project a productive and competitive agricultural sector.